Field reports form for submitting seasonal observations of Iowa birds, Robert I. Cecil, fall 1988 - Cecil, Robert I.et al (1988)
List of birds and locations contributed by Robert I. Cecil with observers Francis L. Moore, John Cecil, Thomas H. Kent and others. The field notes include an attached page with detailed descriptions of a Lesser Yellowlegs, Black-bellied Plover and a Greater Scaup. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed